2020
DOI: 10.1177/2235042x20920458
|View full text |Cite
|
Sign up to set email alerts
|

The benefits and harms of therapeutic exercise on physical and psychosocial outcomes in people with multimorbidity: Protocol for a systematic review

Abstract: Aim: The aim of this study is to investigate the benefits and harms of therapeutic exercise in people with multimorbidity defined as the combination of two or more of the following conditions: knee and hip osteoarthritis, hypertension, diabetes type 2, depression, heart failure, ischaemic heart disease and chronic obstructive pulmonary disease, by performing a systematic review of randomized controlled trials (RCTs). Methods: This study will be performed according to the recommendations from the Cochrane Colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…This systematic review with meta-analysis has been conducted and reported according to recommended international guidelines ( Higgins et al, 2019 ; Moher et al, 2009 ) and it followed a pre-specified protocol ( Bricca et al, 2020 ). Additionally, we have contacted study authors to retrieve missing information from the included RCTs which allowed us to conduct meta-regression analyses with complete data for intervention characteristics such as mode of delivery and setting of the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This systematic review with meta-analysis has been conducted and reported according to recommended international guidelines ( Higgins et al, 2019 ; Moher et al, 2009 ) and it followed a pre-specified protocol ( Bricca et al, 2020 ). Additionally, we have contacted study authors to retrieve missing information from the included RCTs which allowed us to conduct meta-regression analyses with complete data for intervention characteristics such as mode of delivery and setting of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for this systematic review has been published, ( Bricca et al, 2020 ) and it was registered at PROSPERO (CRD42020150628). The statistical analysis plan was made publicly available on the Open Science Framework website ( Foster and Deardorff, 2017 ) ( https://osf.io/38fcg/ ) before the title and abstract (TIAB) screening phase was initiated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines (PRISMA Checklist: Additional file 1 ) [ 22 ] and was based on a protocol with pre-specified study selection, eligibility criteria, data extraction and strategy for data synthesis [ 23 ] in accordance with the Cochrane Handbook for Systematic Reviews of Interventions [ 24 ]. The protocol was registered at PROSPERO (CRD42020161329) and was also made publicly available via the Open Science Framework website [ 25 , 26 ] before completion of the title/abstract screening phase.…”
Section: Methodsmentioning
confidence: 99%
“…We used the same search strategy developed from our previous systematic review which investigated the effect of exercise therapy in people with multimorbidity [ 23 ]. Information was retrieved from the following sources: Searching MEDLINE via PubMed, EMBASE via Ovid, CINAHL (including preCINAHL) via EBSCO and the Cochrane Central Register of Controlled Trials (CENTRAL) up to October 12, 2019, with no restriction on language.…”
Section: Methodsmentioning
confidence: 99%